2016
DOI: 10.5489/cuaj.3787
|View full text |Cite
|
Sign up to set email alerts
|

Management of adult concealed penis using a meshed, split-thickness skin graft

Abstract: Cite as: Can Urol Assoc J 2016;10(11-12):E407-11. http://dx.doi.org/10.5489/cuaj.3787 Published online November 10, 2016. AbstractIntroduction: Concealed penis (CP) is a rare problem faced by urologists and plastic surgeons. CP occurs secondary to trauma, obesity, or infection. Surgical treatment is individualized and based on patient and provider variables. We aim to review our recent experience using meshed split-thickness skin grafting (STSG) for CP management. Methods: A retrospective review was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…An early series in the plastic surgery literature utilized full thickness skin grafts from the abdominal pannus [10] . However, split-thickness skin grafts have become the modality of choice in the urologic literature [5,6,13,16,17,[19][20][21][22] . Split-thickness skin grafts have the advantage of maximizing graft take rates, while being universally available (usually from the thigh).…”
Section: Surgical Steps -Release Of the Buried Penismentioning
confidence: 99%
“…An early series in the plastic surgery literature utilized full thickness skin grafts from the abdominal pannus [10] . However, split-thickness skin grafts have become the modality of choice in the urologic literature [5,6,13,16,17,[19][20][21][22] . Split-thickness skin grafts have the advantage of maximizing graft take rates, while being universally available (usually from the thigh).…”
Section: Surgical Steps -Release Of the Buried Penismentioning
confidence: 99%
“…The incidence of the CP has not been systematically studied, althougha Japanese study reported a prevalence of 3.7% in male newborn infants [5]. In addition to the abnormal appearance, CP might exert symptoms and negative psychological effects, such as anxiety and/or depression, on children and their parents [6].Spinoit et al [7] had observed abnormal histology of the dartos fascia in 74% of patients with CP and dartos layer of penises then became nonelastic which prevents forward extension of the penis and entrapped it under the pubis. The CP remained a challenge for urologists and a exible surgical approach might be required [2].…”
Section: Introductionmentioning
confidence: 99%
“…Anatomically it is described as when the penis is located beneath the abdomen, thigh or scrotum [ 1 , 2 ]. It is important to note that the penis has a normal corporal length, but poor phallic exposure, and so is distinguishable from conditions such as micropenis [ 3 ]. In cases of buried penis, the penile shaft lies ‘below the prepubic skin’ and is no longer visible due to complete burying.…”
Section: Introductionmentioning
confidence: 99%
“…Complex buried penis is used for cases in which there are multiple causative factors resulting in burial of the penis – for example, patients suffering from both obesity and lymphoedema. Inevitably these patients prove very difficult to treat, often requiring multiple surgeries, delayed healing and a longer time to achieve satisfactory postoperative results [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation